A Rare Case Report on Sewing Needle as an Interdental Aid: Ignorance or Paucity of Oral Health Education - Shakya, Royasa; Koirala, Bandana; Birajee, Gajendra; Pasvan, Chandrakant (Journal of Nepalese Association of Pediatric Dentistry, 2021)
The regular use of interdental aids for maintenance of oral hygiene is relatively sparse especially in the developing countries like Nepal. Rather, use of home-based alternatives is more popular among people, which may cause injury to both the hard and soft tissues of oral cavity. This case reports a 14-year-old-female patient who used sewing needle for removing lodged food which broke and got embedded in the buccal mucosa. Exploration of the site of injury revealed the broken needle which was retrieved under topical anaesthesia. Lack of awareness is still a major hindrance causing poor oral hygiene practices among people. Promotion of effective oral health at all levels is the need of hour for achieving holistic health care of especially the dependent population. It is thus high time that we, as dentists evaluate our role in the society and ponder upon the oral health education provided to patients regarding oral health.